Mechanism of Rhinovirus Immunity and Asthma - Yang, Zuqin; Mitländer, Hannah; Vuorinen, Tytti; Finotto, Susetta (Frontiers in Immunology, 2021)
The majority of asthma exacerbations in children are caused by Rhinovirus (RV), a positive sense single stranded RNA virus of the Picornavirus family. The host has developed virus defense mechanisms that are mediated by the upregulation of interferon-activated signaling. However, the virus evades the immune system by inducing immunosuppressive cytokines and surface molecules like programmed cell death protein 1 (PD-1) and its ligand (PD-L1) on immunocompetent cells. Initially, RV infects epithelial cells, which constitute a physiologic mucosal barrier. Upon virus entrance, the host cell immediately recognizes viral components like dsRNA, ssRNA, viral glycoproteins or CpG-DNA by host pattern recognition receptors (PRRs). Activation of toll like receptors (TLR) 3, 7 and 8 within the endosome and through MDA-5 and RIG-I in the cytosol leads to the production of interferon (IFN) type I and other antiviral agents. Every cell type expresses IFNAR1/IFNAR2 receptors thus allowing a generalized antiviral activity of IFN type I resulting in the inhibition of viral replication in infected cells and preventing viral spread to non-infected cells. Among immune evasion mechanisms of the virus, there is downregulation of IFN type I and its receptor as well as induction of the immunosuppressive cytokine TGF-β. TGF-β promotes viral replication and is associated with induction of the immunosuppression signature markers LAP3, IDO and PD-L1. This article reviews the recent advances on the regulation of interferon type I expression in association with RV infection in asthmatics and the immunosuppression induced by the virus.